Acupuncture Versus Sham Acupuncture: A Meta-Analysis on Evidence for Longer-term Effects of Acupuncture in Musculoskeletal Disorders. Issue 7 (July 2020) - Lenoir, Dorine; De Pauw, Robby; Van Oosterwijck, Sophie; Cagnie, Barbara; Meeus, Mira
Abstract : Editorial Note: : The original Letter to the Editor prepared by Jones et al was based on the initial electronic version then contained several important procedural errors that resulted in erroneous conclusions as noted by Jones et al in their original Letter. Subsequently, the authors of the Letter to the Editor were notified of the corrections and they then prepared the revised Letter to the Editor published here. Jones et al did note a remaining error in Table 5 of their corrected manuscript. Based on Jones et al's observation, Lenoir et al were notified of an error on Table 5 and have addressed this in the current version of their paper published in this issue. We appreciate the input of the authors of the letter and the positive response of the author(s) of this article. Dennis C. Turk, PhD Editor-in-Chief Objective: Acupuncture is a common modality in the therapy of musculoskeletal disorders. The evidence for acupuncture has been examined frequently, but a clear synthesis of previous research is currently lacking. This meta-analysis aimed to summarize the evidence for nonimmediate effects of acupuncture on pain, functionality, and quality of life in patients with musculoskeletal disorders, when compared with sham acupuncture. Methods: Search results from PubMed and Web of Science were brought together. All screening procedures were executed twice by 2 independent researchers. The pooled standardized mean difference (SMD) with its confidence interval (CI) was estimated at follow-up at <1 month, 1 to 3 months, 3 to 6 months, and >6 months. Results: For pain, the SMD equalled respectively −0.47 (CI −0.76 to −0.19), −0.27 (CI −0.44 to −0.11), −0.32 (CI −0.51 to −0.13) and −0.12 (CI −0.36 to 0.11) for <1 month, 1 to 3 months, 3 to 6 months, and >6 months follow-up. For functionality, the pooled SMD equalled −0.43 (CI −0.76 to −0.10), −0.41 (CI −0.76 to −0.05), 0.07 (CI −0.22 to 0.36), and −0.13 (−0.46 to 0.19). In the area of QOL, pooled SMD of respectively 0.20 (CI 0.04 to 0.35), 0.19 (CI −0.01 to 0.39), 0.02 (CI −0.09 to 0.14) and −0.04 (CI −0.25 to 0.16) were obtained. Discussion: A significant difference in therapy effect, favoring acupuncture, was found for pain at <1 month, 1 to 3 months, and 3 to 6 months, as well as on quality of life at <1 month, and on functionality at <1 month and 1 to 3 months. Abstract : Supplemental Digital Content is available in the text.